Precision Forging Technics and Precision Forging Machining Experiment of Driven Spiral Bevel Gear - Zhang Hua; Chen Jianfei; Yang Jianjun; Li Tianxing; Li Jubo (Jixie chuandong)
In actual gear manufacturing,there is a large part of spiral bevel gears with big transmission ratio,and its driven gear cone angle is larger than sixty degrees. The above driven gear can be produced by precision forging technics,and the pinion can be produced by traditional face- milling method to match for the forging gear. According to the process method mentioned upon,the tooth surface machining parameters which ensure spiral bevel gear has good meshing performance is designed. And according to the accurate machining parameters,spiral bevel gear 3D model can be created. This 3D model can be used to make driven gear precision forging mould. A pair of spiral bevel gears is used as an machining experiment example,the driven gear is made by precision forging process,and the pinion gear is milled to match for gear,the mesh rolling test shows that the tooth surface contact bearings are good. The carrying out of this precision forging process is beneficial to improving the machining efficiency of spiral bevel gear,reducing energy consumption,enhancing the gear strength,it must has a broad application prospect.